The Influence of Competence and Motivation on Teacher Performance at SMA Negeri 1 Tapango Polewali Mandar Regency - Magfirah; Ady DJ, Arifhan; Asyraf, Ammar (MANDAR: Management Development and Applied Research Journal, 2025)
This study aims to analyze the influence of competence and motivation on teacher performance at SMA Negeri 1 Tapango, Polewali Mandar Regency. The method used was quantitative research with 40 teachers as the sample, selected using a saturated sampling technique. Data was collected through a questionnaire measuring the variables of competence, motivation, and teacher performance, and analyzed using multiple linear regression, which was then processed using Statistical Product and Service Solutions (SPSS). The results of this study indicate that competence has a positive and significant effect on teacher performance with a regression coefficient of 0.603, while motivation also has a positive and significant effect with a regression coefficient of 0.257. The simultaneous test shows that the variables of competence and motivation have a significant effect on teacher performance with a calculated F value of 58.413. These findings indicate that improving teachers' competence and motivation can enhance their performance. Keywords: Competence, Motivation, and Teacher Performance